Comparative Study on the Nutritional Profile of Cultured and Captured African Catfish (Clarias gariepinus) - OBOH, Ijeoma Patience; EGUN, Nkonyeasua Kingsley; OLOWO, Ukpamufo Cyril (Aquatic Life Sciences, 2026)
Aquaculture contribution to human nutrition, consumers’ preferential bias towards capture fisheries and concerns on food safety has necessitated the need for information on the nutritional composition of fish species from diverse settings such as geographical locations and aquaculture rearing facilities. This study determined the nutritional profile and associated human health risk of adult size African catfish (Clarias gariepinus) cultured in plastic tanks with those harvested from the wild. Results showed the mean protein (18.04%) and lipid (8.71%) values of cultured C. gariepinus were significantly higher than reported values in C. gariepinus from the wild, which makes them of more nutritional value to consumers. Captured fishes reported higher ash, mineral and trace metal contents, which was attributed to the elevated levels of these elements in their habitat waters due to water pollution. Low metal pollution index (MPI) values in cultured and captured fishes indicated an insignificant bioaccumulation of trace metals, and the absence of non – carcinogenic (HI <1) and carcinogenic (ICR < 1 × 10−6) risk associated with their consumption. Although the captured fishes at present poses no health risk to consumers; their recorded higher contents of trace metals, MPI, HI and CPI values is a cause for concern on the safe consumption of capture fishes. With increasing concerns on aquatic food safety, this study has shown that the consumption of cultured C. gariepinus provides more nutritional quality to consumers. The need for more monitoring studies on different culturing methods and settings on the nutritional composition and food safety is recommended.